False alarm, nuclear danger. - Forden, G. (IEEE spectrum)
The radar and satellite networks meant to warn Russia of the imminence of a missile attack are breaking down, heightening the risk of accidental nuclear war. The authors discuss the reasons for the this which include ageing satellites and the floundering Russian economy. The authors discuss a false alarm in 1995 and how it highlighted the deficiencies in Russia's early warning system. The state of the satellites involved in early warning systems, both Russian and American, are discussed. The offer of assistance by the US to Russia with respect to Russia's early warning systems is also discussed